GO clad Co3O4 (Co3O4@GO) as ORR catalyst of anion exchange membrane fuel cell. (3rd August 2017) - Wang, Dong-Chao; Huang, Nai-Bao; Sun, Yin; Zhan, Su; Zhang, Jun-Jie
Abstract: GO cladded Co3 O4 (Co3 O4 @GO core/shell) was synthesized as ORR catalyst for anion exchange membrane fuel cell (AEMFC) by ultrasonic method. The obtained GO/Co3 O4 was characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), high-resolution transmission electron microscopy (HRTEM), and Fourier transform infrared spectroscopy (FT-IR). Physical characterizations confirmed the obtained catalyst was composed of GO lamina (2 nm) shell and 10 nm Co3 O4 nanoparticle core. The optimal content of GO was 5%. At the moment, its onset potential and polarized current density were identical with that of commercial 20% Pt/C catalyst. The limited current density for ORR reached 4.30 mA cm −2, which was smaller than that of 20% Pt/C (4.62 mA cm −2 ). The prepared Co3 O4 @GO/C catalyst behaved excellent cycle stability after 1000th cycle. The results indicated the prepared Co3 O4 @GO/C maybe a potential, efficient and low cost catalyst for ORR in AEMFC. Highlights: Co3 O4 @GO core/shell catalyst was synthesized as ORR for AEMFC by ultrasonic method. The Co3 O4 @GO was composed of GO lamina (2 nm) shell and 10 nm Co3 O4 nanoparticle core. The best activity of Co3 O4 @GO was similar to that of commercial 20% Pt/C catalyst.